Recent Advances in Regenerative Tissue Fabrication: Tools, Materials, and Microenvironment in Hierarchical Aspects. Issue 5 (6th May 2021) - Ratri, Monica Cahyaning; Brilian, Albertus Ivan; Setiawati, Agustina; Nguyen, Huong Thanh; Soum, Veasna; Shin, Kwanwoo
Abstract : Hierarchical Tissues As part of regenerative medicine, tissue engineering is a favorable approach to satisfy the needs of patients for new tissues and organs. In article number 2000088, Kwanwoo Shin and co‐workers introduce the biological requirements and the recent technical strategies to achieve hierarchical architectures in tissue engineering. The cover image illustrates a cross section image of the skin, composed of multilayered tissues as an example of living organs with hierarchical architectures in nature.